The Sequential Organ Failure Assessment (SOFA) Score - Moreno, Rui (2023)
Funding Information: RM has no competing interest to declare relevant to this article. AR has no competing interest to declare relevant to this article. LP has no competing interest to declare relevant to this article. GH has no competing interest to declare relevant to this article. JT has no competing interest to declare relevant to this article. HBG received funding from Gilead Sciences, Inc. to serve on COVID therapeutics advisory board (not related to this work). MT has no competing interest to declare relevant to this article. CMC is an Associate Editor of Critical Care—he has no other competing interest to declare relevant to this article. SNM has no competing interest to declare relevant to this article. Mervyn S has no competing interest to declare relevant to this article. ER has no competing interest to declare relevant to this article. HCP served on the surviving sepsis campaign guidelines and is physician-lead for a Michigan statewide sepsis consortium. This manuscript does not represent the views of the Department of Veterans Affairs or the US government. This material is the result of work supported with resources and use of facilities at the Ann Arbor VA Medical Center. Marcio S is founder and equity shareholder of Epimed Solutions®, which commercializes the Epimed Monitor System, a cloud-based software for ICU management and benchmarking. JFT has no competing interest to declare relevant to this article. DWdL has no competing interest to declare relevant to this article. CJ has no competing interest to declare relevant to this article. JJDW has no competing interest to declare relevant to this article. GSM has no competing interest to declare relevant to this article. CS has no competing interest to declare relevant to this article. EA has no competing interest to declare relevant to this article. AR has no competing interest to declare relevant to this article. TF has no competing interest to declare relevant to this article. ASM has no competing interest to declare relevant to this article. JLV is Editor-in-Chief of Critical Care—he has no other competing interest to declare relevant to this article. ® Funding Information: JJDW is supported by a Senior Clinical Investigator Grant from the Research Foundation Flanders (FWO, Ref. 1881020N). Publisher Copyright: © 2023, The Author(s).